A trip to Riviera Maya, Tulum, Sankan Researve Forest, Quinta Roo and Chichenitza, Yucanta: Regions of Mega Biodiversity and Antique Maya culture - Maiti, Ratikanta; Maiti, Sandip (International Journal of Bio-resource and Stress Management, 2023)
We made a joyous and educational trip from 26 June to 6th July, 2014 to Riviera Maya, Tulum, Sian Ka’an Reserve forest, Punta de Allen, Qintanaroo and Chichen Itza, Yucatan, Sothern regions of Mexico. The enchanting nature the beauty and biodiversity of plants and wild animals remain a reflection of ancient Mayan Culture. We got down from our two hour flight from Monterrey to Cancun and started a long but enjoyable trip through great diversity of trees and shrubs in tropical rainforests in the tourist van before we arrived at our hotel.